Within-visit blood pressure variability and cardiovascular risk factors in hypertensive patients with non-dialysis chronic kidney disease. (3rd October 2017) - Azushima, Kengo; Wakui, Hiromichi; Uneda, Kazushi; Haku, Sona; Kobayashi, Ryu; Ohki, Kohji; Kinguchi, Sho; Haruhara, Kotaro; Fujikawa, Tetsuya; Toya, Yoshiyuki; Umemura, Satoshi; Tamura, Kouichi
ABSTRACT: As there may be an association between within-visit blood pressure (BP) variability and cardiovascular disease (CVD), we investigated the clinical significance of this BP variability in non-dialysis chronic kidney disease (CKD) patients. Materials and methods : According to the median of coefficient of variation (CV) of three systolic BP (SBP) readings within a single visit, we divided hypertensive patients with stage G1-4 CKD already treated with antihypertensive therapy into the high SBP-CV group and the low SBP-CV group. Univariate and multivariate linear regression analyses were also performed to explore the contributing factors to within-visit BP variability. Results : In the high SBP-CV group, the clinic BP, total cholesterol level, dyslipidemia, and past history of CVD were significantly greater, while α1 -blockers and renin-angiotensin system (RAS) inhibitors usage were significantly reduced compared with the lower SBP-CV group. Within-visit BP variability was significantly and positively correlated with total cholesterol ( R = 0.392, P < 0.001) and low-density lipoprotein cholesterol ( R = 0.284, P = 0.013). Total cholesterol ( β = 0.269, P = 0.024), α1 -blockers usage ( β = −0.260, P = 0.015), and RAS inhibitors usage ( β = −0.266, P = 0.017) were shown to independently contribute to the within-visit BP variability after adjustment for age, sex, presence of diabetes, CVD history, statins usage, and clinic SBP. Conclusions : We show that within-visit BP variability may be a clinically relevant factor of CVD risk, and lipid lowering and/or anti-hypertensive therapies using RAS inhibitors and α1 -blockers may be associated with the improved within-visit BP variability observed in non-dialysis CKD patients.